Answer:
What you need help with? I don't see a question or anything
Step-by-step explanation:
Yes u can. It is very easy
Answer:
(
−
2
)
=
−
1
4
(
−
8
)
(x-2)=\frac{-1}{4}(x-8)
(x−2)=4−1(x−8)
Solve
1
Eliminate redundant parentheses
(
−
2
)
=
−
1
4
(
−
8
)
−
2
=
−
1
4
(
−
8
)
2
Combine multiplied terms into a single fraction
−
2
=
−
1
4
(
−
8
)
−
2
=
−
1
(
−
8
)
4
3
Distribute
−
2
=
−
1
(
−
8
)
4
−
2
=
−
+
8
4
4
Add
2
2
2
to both sides of the equation
−
2
=
−
+
8
4
−
2
+
2
=
−
+
8
4
+
2
5
Simplify
Add the numbers
=
−
+
8
4
+
2
Solution
=
1
6
5
Step-by-step explanation:
Actually, when you know 2 sides and an included angle, you use the Law of Cosines. (and we don't know if theta is an included angle).
Solving for side c
c^2 = a^2 + b^2 -2ab * cos(C)
c^2 = 36 + 16 - 2*6*4 * cos(60)
c^2 = 52 -48*.5
c^2 = 28
c = 5.2915
Using the Law of Sines
side c / sin(C) = side b / sin (B)
5.2915 / sin(60) = 4 / sin (B)
sin(B) = sin(60) * 4 / 5.2915
sin(B) = 0.86603 * 4 / 5.2915
<span><span>sin(B) = 3.46412
</span>
/ 5.2915
</span>
<span><span><span>sin(B) = 0.6546571451
</span>
</span>
</span>
Angle B = 40.894 Degrees
sin (A) / side a = sin (B) / side b
sin (A) = 6 * sin (40.894) / 4
sin (A) = 6 * 0.65466 / 4
sin (A) = .98199
angle A = 79.109 Degrees
angle C = 60 Degrees
Step-by-step explanation: